Phonological and Musical Loops in Live Coding Performance Practice. - KIM-BOYLE, DAVID (Leonardo Music Journal, 2017)
This paper explores how various phenomena of working memory are actively drawn on and can provide useful insights into live coding performance practice. The author argues that the phonological coding processes that cognitive psychologists believe underscore how auditory information is retained and recollected in working memory can enrich our understanding of live coding performance practice, where loopbased processes often provide key structural units. The author suggests that such practice finds structural coherence and aesthetic value through a real-time play with the effects of working memory.